MIDWIFE CARE IN THE 1st TRIMESTER PREGNANT WOMEN WITH A INTERVENTION FOCUS ON GENERATION OF GINGER OIL THERAPY TO REDUCE NATURE OF VOMITING PATIENT HYPEREMESIS GRAVIDARUM IN PUSKESMAS TOROH I - Santi Hermawati Umaroh; Nurya Kumalasari; Dhiyan Nany Wigati (The Shine Cahaya Dunia Kebidanan, 2023)
Background; Hyperemesis gravidarum or nausea and vomiting that occurs in pregnancy caused by increased levels of the hormones estrogen and progesterone produced by Human Chorionic Gonadotropine (HCG) in the serum of the placenta. Nausea and vomiting occurs in 60-80% of primigravidas and 40-60% of multigravidas. Hormonal changes in every pregnant woman will respond differently, so not all experience nausea and vomiting during pregnancy. Nutritional disorders, dehydration, weakness, weight loss and electrolyte imbalance. Apart from experiencing excessive nausea and vomiting or what is called hyperemesis gravidarum during pregnancy, it not only threatens the life of pregnant women, but can also cause side effects on the fetus such as abortion, low birth weight babies, and also premature birth. Method The research design that researchers use is a case study research design. This type of descriptive case study research uses participatory observation methods. The subjects in this study were pregnant women in the first trimester of 11 weeks pregnant. Results; The results of the study showed that Mrs. M was diagnosed by giving ginger oil aromatherapy. Evaluation of the implementation of ginger oil aromatherapy in Mrs.M’s case by giving ginger oil aromatherapy to reduce the frequency of nausea and vomiting in pregnant women. Conclusion; There was a decrease in the frequency of nausea and vomiting in pregnant women after being given ginger oil aromatherapy treatment.